If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(3x + -5) = 4(6x + 3) Reorder the terms: 8(-5 + 3x) = 4(6x + 3) (-5 * 8 + 3x * 8) = 4(6x + 3) (-40 + 24x) = 4(6x + 3) Reorder the terms: -40 + 24x = 4(3 + 6x) -40 + 24x = (3 * 4 + 6x * 4) -40 + 24x = (12 + 24x) Add '-24x' to each side of the equation. -40 + 24x + -24x = 12 + 24x + -24x Combine like terms: 24x + -24x = 0 -40 + 0 = 12 + 24x + -24x -40 = 12 + 24x + -24x Combine like terms: 24x + -24x = 0 -40 = 12 + 0 -40 = 12 Solving -40 = 12 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 8x+6-9x=2 | | 3x+2x+5=4x-2 | | (1-w)(3w-5)=0 | | -2x-3=-9 | | 3w-5=0 | | 14x-2=0 | | 3y=-5x+12 | | 9z=-45 | | 8x-4x+2=48 | | x^3-x^2-16=20 | | 8(3x-5)=(6x+3) | | 2Inx=4 | | y=5-5x | | 2x+5=156 | | 10+m=19-2m | | m^3+27n^3=0 | | X^2+8=-9 | | 3(x-2)-18=0 | | x+3+2x-2=128 | | -4+5=-5 | | 2x+2=6x+4 | | -15y=-195 | | 20+x=5 | | 7x-13=24 | | -7=x+8 | | d-1=-23 | | 11z=-88 | | -5x=-5 | | 4x-7=x+5 | | 2t^2-8t-15=0 | | 9x-8=12x+3 | | 8x-(6x+5)=3x-33 |